From local to global: systematically reviewing higher education internationalization in Asia - Sukjairungwattana, Paisan; Hu, Haiyang; Liu, Ruijia; Huang, Jiayan (Frontiers in Education, 2025)
With the advancement of globalization, English as a key resource for knowledge, business, and culture has become increasingly important in higher education. This study aims to explore the challenges of English education in the process of internationalization of higher education in Asia, especially in China. This study systematically reviews relevant literature associated with Asian countries, focusing on the impact of English-medium instruction (EMI) courses on student performance in China, Japan, and Central Asia. The findings indicate that while English education provides students with broader international communication opportunities, it also poses challenges in terms of cultural identity and academic performance. Furthermore, changes in policies and practices have had a profound impact on the experiences of teachers and students, especially in the context of international schools and education centers.